Precarious transition: a mortality study of South African ex-miners - Kim Bloch; Leigh F. Johnson; Mlindeli Nkosi; Rodney Ehrlich (BMC, 2018)
Abstract Background Despite their burden of a triple epidemic of silicosis, tuberculosis and HIV infection, little is known about the mortality experience of miners from the South African mining industry once they leave employment. Such information is important because of the size and dispersion of this population across a number of countries and the progressive nature of these diseases. Methods This study included 306,297 South African miners who left the industry during 2001-2013. The study aimed to calculate crude and standardised mortality rates, identify secular trends in mortality and model demographic and occupational risk factors for mortality. Results Crude mortality rates peaked in the first year after exit (32.8/1000 person-years), decreasing with each year from exit. Overall mortality was 20% higher than in the general population. Adjusted annual mortality halved over the 12 year period. Mortality predictors were being a black miner [adjusted hazard ratio (aHR) 3.30; 95% confidence interval (CI) 3.15-3.46]; underground work (aHR 1.33; 95% CI 1.28-1.39); and gold aHR 1.15 (95% CI 1.12-1.19) or multiple commodity employment (aHR 1.15; 95% CI 1.11-1.19). Conclusions This is the first long-term mortality assessment in the large ex-miner population from the South African mining industry. Mortality patterns follow that of the national HIV-tuberculosis epidemic and antiretroviral treatment availability. However, ex-miners have further elevated mortality and a very high mortality risk in the year after leaving the workforce. Coordinated action between the mining industry, governments and non-governmental organisations is needed to reduce the impact of this precarious transition.